2011
DOI: 10.1111/j.1475-2743.2011.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon and related soil properties along a soil type and land‐use intensity gradient, New South Wales, Australia

Abstract: The aim of this study was to systematically quantify differences in soil carbon and key related soil properties along a replicated land‐use intensity gradient on three soil landscapes in northwest New South Wales, Australia. Our results demonstrate consistent land‐use effects across all soil types where C, N and C:N ratio were in the order woodland > unimproved pasture = improved pasture > cultivation while bulk density broadly showed the reverse pattern. These land‐use effects were largely restricted to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 41 publications
(77 reference statements)
7
19
1
Order By: Relevance
“…The results most directly comparable with ours are those for Wilson et al (2011) who assessed the effect of land use on carbon levels of soils in the Northern Tablelands and Northwest Slopes of NSW. They present their results by 5 cm depth intervals allowing calculation of carbon density for 0-10 cm for comparison with our results.…”
Section: Level Of Carbonsupporting
confidence: 77%
See 1 more Smart Citation
“…The results most directly comparable with ours are those for Wilson et al (2011) who assessed the effect of land use on carbon levels of soils in the Northern Tablelands and Northwest Slopes of NSW. They present their results by 5 cm depth intervals allowing calculation of carbon density for 0-10 cm for comparison with our results.…”
Section: Level Of Carbonsupporting
confidence: 77%
“…Similar to the findings of Young et al (2005) and Wilson et al (2011), there was no interaction between soil texture and land use history, that is, the effects of land use were similar on soils of varying clay content.…”
Section: Effect Of Soil Texturesupporting
confidence: 72%
“…Land use, as represented by LDI is shown to have a relatively low influence on SOC levels at this sub-continental scale, but it may be at least partly masked by the vegetation cover factor. Its influence appears to decline further with depth, similarly reported by others (Luo et al, 2010;Wilson et al, 2010Wilson et al, , 2011Allen et al, 2013;Badgery et al, 2013), Nevertheless the factor is still considered important in subsoils (Guo and Gifford, 2002;Wright et al, 2007;Meersmans et al, 2009;Follett et al, 2009;Vasques et al, 2010;Rumpel and Kögel-Knabner 2011). It has been suggested that SOC in deeper soil layers might reflect historic rather than current land use (Schulp and Veldkamp, 2008;Wilson and Lonergan, 2013).…”
Section: Influence Of Individual Factors Driving Soil Organic Carbon mentioning
confidence: 52%
“…It becomes the clearly dominant influence in the mid and lower layers. The importance of parent material in controlling SOC has also been reported by several recent workers (Mishra et al, 2012;Chaplot et al, 2010;Vasques et al, 2010;Powers et al, 2011;Wilson et al, 2011;Cotching, 2012;Badgery et al, 2013;Viscarra Rossel et al, 2014). Its influence is primarily due to its control of soil texture and clay content which serves to protect SOC from mineralization (Oades, 1988;Paustian et al, 1997;Baldock and Skjemstad, 1999;Baldock et al, 2009b;Heckman et al, 2009) and its control of soil fertility and nutrient supply to promote production of organic material (Badgery et al, 2013).…”
Section: Influence Of Individual Factors Driving Soil Organic Carbon mentioning
confidence: 74%
“…The maps deserve consideration during any climate change mitigation programs that are based on increased soil C sequestration (Lal et al, 2007;Wilson et al, 2011;Baldock et al, 2012;Smith, 2012). Those regions of NSW, where the soil C storage has been shown to have a declining trend, such as in the east and south, will require even greater C-enhancing actions to produce the desired soil C increases.…”
Section: Application Of the Soc Change Mapsmentioning
confidence: 99%